DigComp and MIL frameworks contribute to fight fake news and disinformation - Ançanello, Juliana Venancio [UNESP] (2023)
Introduction: The consumption of information and news in the virtual environment, characterized by infinite content, permanent connection and information overload, makes it difficult to discern what is or is not factual information. Objective: The objective is to investigate what are the guidelines proposed by the DigComp and MIL documents to prepare individuals against fake news and misinformation. Methodology: Content Analysis, more specifically categorical analysis, was used to analyze the selected frameworks. Three analysis categories were created with seven inferences. Results: In the Key Concepts category, only misinformation inference is presented in both documents. There are recommendations for the evaluation of information in nontraditional information environments, as inferred in category two in both analyzed frameworks. It was found that DigComp brings specific guidelines regarding the Skills, Knowledge and Attitudes category, while the MIL includes two of the three inferences proposed in the category. Conclusion: The documents offer a set of conceptual, pedagogical and strategy-action references that provide guiding elements for the preparation of users, and it is imperative that information professionals are proactive in relation to misinformation and fake news, in addition to knowing, analyzing and criticizing the available references to develop strategies based on the integration of different skills to prepare subjects to use non-traditional informational environments.